DOCK8 deficiency and diagnostic guidelines for hyper-IgE syndromes - Engelhardt, K.; Gertz, E.; Keles, S.; Schaeffer, A.; Ceja, R.; Sassi, A.; Grimbacher, B. (Wiley-Blackwell, 2012)
[Abstract Not Available]
31st Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) -- JUN 16-20, 2012 -- Geneva, SWITZERLAND